The Iconic Of River Of Life - Ishak, Mohd Nur Ihsan; Zainal, Hanum Ain; Adnan, Azzatul Shima (MAJ - Malaysia Architectural Journal, 2025)
Iconic projects, such as the River of Life, Pintasan Saloma, Kuala Lumpur Gantry, Urban Place Making, Heritage Walk, Urban Back Lane, Bangunan Sultan Abdul Samad, and KL Street Beatification, are significant construction or development endeavours with symbolic significance, extraordinary design, innovation, or cultural impact. These projects, often serving as landmarks or representations of a city, region, or concept, are notable for their architectural uniqueness, historical importance, or ability to capture public attention and admiration. Therefore, efficient and persistent maintenance plans are crucial. Iconic projects in big cities contribute to the country’s financial, political, and cultural success. Facility management involves a team of professionals, including architects, civil engineers, and quantity surveyors, and should incorporate thorough planning into daily building operation. The Klang riverfront, a significant natural treasure in Greater Kuala Lumpur, is undergoing restoration to become a major city. The restoration aims to educate people and in still a sense of ownership in the city while preserving its heritage. The goal of Kuala Lumpur’s waterfront renovation is to maintain its history while also redefining this desirable area. The River of Life will weave together diverse waterfront areas, strengthening the identity of the area as the historical, physical, and social entities of Kuala Lumpur. The river is home to historical structures such as Merdeka Square, and Masjid Jamek, symbolizing the initiation of Kuala Lumpur. The River of Life offers stunning views of the City Center, making it the most unique KL river corridor. The restoration has beautified the river, reinvigorating its social and cultural legacy, ecology, and environmental consciousness. The project has received numerous accolades, including the 2014 ISOCARP Awards, the 2015 Malaysia Landscape Architecture Awards, the 2015 Singapore Landscape Architecture Awards, and the 2021 LivCOM Awards in collaboration with the United Nations Environment Programme (UNEP).